2012
DOI: 10.2298/mpns1210436n
|View full text |Cite
|
Sign up to set email alerts
|

A case of severe ADAMTS 13 deficiency presenting as thrombotic thrombocytopenic purpura in pregnancy

Abstract: Severe ADAMTS 13 deficiency may present as thrombotic thrombocytopenic purpura of pregnancy. Pregnant women with thrombotic thrombocytopenic purpura and especially with severe deficiency of ADAMTS13 levels require specific consideration regarding treatment and prophylaxis in subsequent pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Pregnancyrelated hypercoagulability and decline of ADAMTS13 levels are the reasons (45). Especially in severe ADAMTS13 deficiency, TTP develops during pregnancy (46). The risk of recurrence after pregnancy is high.…”
Section: Adamts In the Pathogenesis Of Obstetrics And Gynecology Disementioning
confidence: 99%
“…Pregnancyrelated hypercoagulability and decline of ADAMTS13 levels are the reasons (45). Especially in severe ADAMTS13 deficiency, TTP develops during pregnancy (46). The risk of recurrence after pregnancy is high.…”
Section: Adamts In the Pathogenesis Of Obstetrics And Gynecology Disementioning
confidence: 99%
“…Most of women with cTTP commonly develop the microangiopathic hemolytic anemia and thrombocytopenia during pregnancy. 7,12,13 Ferrari et al 6 reported a patient who was presented with unexplained hemorrhages presumably due to thrombocytopenia in infancy and was followed up with a misdiagnosis as Evans syndrome until 57 years old. 6 In conclusion, cTTP is a very rare condition that present with microangiopathic hemolytic anemia and thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…It is usually effective, with a non-response rate of up to 8% in some reports and a survival rate of 70% at 10 years. Although, previously, splenectomy had an increased risk of adverse events, especially when used in refractory TTP, improvements in surgical techniques have significantly reduced complications, especially when using a laparoscopic technique [ 6 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…N-acetylcysteine appeared to inhibit VWF-dependent platelet aggregation, but has currently only been studied in animals. Differential diagnosis with other TMAs (acute microangiopathies) has been very difficult to establish [ 6 , 22 , 23 ]. The relapse rate of this pathology recorded in studies is still relatively high with long-term follow-up and subsequent management being required along with multidisciplinary-instituted therapy [ 17 , 18 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%